Analysis of Reading, Reference and Information Management on the Quality of Scientific Writing - Zarlis, Muhammad; Astuti, Sherly; Salamuddin, Muhammad (APTISI Transactions on Management (ATM), 2018)
In education, for educational instruments scientific writing is a very important thing. It requires an information management skill, information management is a library search, which can be done through a computer and guided by the internet. It can also be through the quality of reading used as a reference for scientific writing. In addition, in producing a paper also must know the management of writing, not only required to pay attention to the rules of standard language, but also must be able to convey ideas and ideas well and meet scientific criteria, such as making a quote or reference list used. This paper was written with the aim of improving the quality of research through reading material, making notes and avoiding plagiarism, references using the Harvard system for journals, books, and articles. Management of citing articles either CD or internet, writing, editing, storing references electronically, writing bibliography, and quotations.